Pengaruh Program Self Diabetes Management Education (SDME) dengan Metoda Kelompok terhadap Dukungan Keluarga dan Kualitas Hidup Pasien Diabetes Mellitus - Ani Nuraeni (Jurnal Health Sains, 2021)
Diabetes mellitus can become serious and cause chronic conditions that are dangerous if left untreated. According to the World Health Organization (WHO) in 2011, diabetics are at risk of microvascular damage such as retinopathy, nephropathy, and neuropathy. This has an effect on the quality of life of DM sufferers.. The quality of life of DM patients can be improved in many ways. One of the methods that has been used to improve the quality of life of DM sufferers is the Self Diabetes Management Education (SDME) method with group methods. Self Diabetes Management Education (SDME) is an ongoing process to facilitate the knowledge, skills and abilities necessary for the self-care of Diabetes Mellitus patients. SDME provides decision making information, self-care behavior, problem solving and active cooperation with health teams and to improve clinical outcomes, health status and quality of life.. This study aims to find out the influence of Self Diabetes Management Education (SDME) with group methods on family support and quality of life of DM sufferers in the working area of Puskesmas Ragunan Village, South Jakarta. This study used Quasi Experiment design with DM patients in Ragunan Village Health Center Pasar Minggu as a sample.